EFFECT OF KECEMCEM (Spondias pinnata) EXTRACT ON ANGIOGENESIS OF GINGIVA AFTER CURETASE OF WISTAR RATS - Eka Pramudita Ramadhany; Media Sukmalia Adibah; I Ketut Suandika Dharma Yanta (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Background: Curettage procedure cause wounds that require adjuvant therapy. One of adjuvant therapies used is hyaluronic acid. However, recently, several studies have focused on antioxidant and anti-inflammatory properties of various natural products such as the bark of  kecemcem tree (Spondias pinnata) which has protective effect against oxidative and inflammatory changes occurs during development of mucositis. Based on this, researchers were interested examining effect of giving kecemcem bark extract on formation of new blood vessels (angiogenesis) in gingiva after curettage. Materials and Methods: Wistar rats were divided into 3 groups, negative control, positive control, and treatment group. Previously, rats had induced periodontal pockets by tying silk threads on mandibular incisors and after that they were curettage using a gracey curette. Negative control group was given CMC-Na, positive control group was given hyaluronic acid and treatment group was given 70% kecemcem bark extract gel. Rats were sacrificed on day 3, 5 and 7 and then histological preparations were made. Results and discussion: Average number of new blood vessels in the treatment group was higher than  control group and positive control with  two-way ANOVA test showed that average number of new blood vessels in each group had significant difference (p<0.05). This supports hypothesis that compounds found in the bark of the kecemcem tree such as beta-sitosterol, phenols, and flavonoids have effect on increasing angiogenesis in gingival wounds after curettage of Wistar rats. Conclusion: 70% kecemcem bark extract gel has effect on increasing angiogenesis in gingival wounds after curettage of Wistar rats.